Synchrotron Radiation Photoemission Electron Microscopy Study on Radioactive Cesium-bearing Microparticle Collected in Fukushima - Yoshigoe, Akitaka; Tsuda, Yasutaka; Kobata, Masaaki; Okane, Tetsuo; Satou, Yukihiko; Ohkochi, Takuo (E-journal of surface science and nanotechnology, 2025)
Synchrotron radiation photoemission electron microscopy (SR-PEEM) combining with hard X-ray photoelectron spectroscopy (HAXPES) was utilized to obtain detailed structural and chemical insights into radioactive cesium-bearing microparticles (CsMPs) smaller than 10 µm, collected from a location 25 km northwest of the Fukushima Daiichi Nuclear Power Plant (FDNPP). X-ray absorption spectromicroscopy with a spatial resolution of approximately 50 nm was employed to investigate the presence of five elements (Cs, Fe, U, Zn, Si) on the microparticle surface. HAXPES data revealed the presence of several elements such as C, O, Mg, Al, Si, Sr, and Cs, while the chemical mapping images obtained by SR-PEEM clearly demonstrated that Cs atoms almost exclusively cover the particle surface. Owing to the surface-sensitive nature of SR-PEEM compared to HAXPES, the results notably indicate inhomogeneous distributions of elements, suggesting an eggshell-like structure with a Cs shell, with a thickness greater than the escape depth of the photoelectrons (a few nanometers) as a most presumable structural model of CsMPs. These novel findings strongly suggest that the aggregation of Cs atoms likely occurs at the microparticle surface and are expected to have applications in the remediation of nuclear power plant accidents.